Lives of the engineers. - Smiles, Samuel, 1812-1904 (John Murray, 1891)
Samuel Smiles's Lives of the Engineers looks at harbours, lighthouses and bridges in this volume before detailing the lives of Smeaton and Rennie.
Includes index.
Keywords: Harbors -- Design and construction -- History.; Lighthouses -- Design and construction -- History.; Bridges -- Design and construction -- History.; Smeaton, John, -- 1724-1792.; Rennie, John, -- 1761-1821.; Engineers -- Great Britain -- Biography.; elektronické knihy; electronic books